Consolidation analysis of soft ground with air-boosted vacuum preloading considering attenuation of vacuum and boost pressure - Weiliang Gao; Lu Han; Yanming Zhao; Jinxin Sun; Lulu Liu (Scientific Reports)
Abstract Air-boosted vacuum preloading (AVP), an innovative soil improvement methodology extensively employed in subgrade enhancement projects, demonstrates exceptional efficacy in accelerating soil consolidation processes and improving load-bearing characteristics of soft foundation. Current understanding remains constrained by insufficient theoretical exploration of AVP consolidation mechanisms, particularly regarding underdeveloped analytical frameworks. Therefore, this investigation establishes an analytical model for AVP-assisted consolidation incorporating attenuation of vacuum and boost pressure. Fundamental governing equations were formulated through rigorous analysis of vacuum load propagation patterns, accounting for pressure dissipation along both vertical and radial coordinates. The proposed solutions integrate PVD-induced soil disturbance effects and three-dimensional fluid migration patterns. Model validation was achieved through systematic degeneration analysis, confirming consistency with established solutions in specific boundary conditions. Parametric sensitivity analysis revealed significant correlations between consolidation efficiency and key operational variables when benchmarking against conventional models. Crucially, computational findings emphasize that neglecting pressure attenuation mechanisms leads to non-conservative estimates of consolidation progression rates. Enhancement of consolidation rate was observed with higher vacuum loading coefficients and increased Poisson ratios. A limitation section is also introduced to provide critical insights into improving the theoretical investigations on the consolidation of AVP-improved ground.